2022
DOI: 10.1039/d2cc04976g
|View full text |Cite
|
Sign up to set email alerts
|

In situ lead oxysalt passivation layer for stable and efficient perovskite solar cells

Abstract: Rb2SO4 additive is employed to passivate the Pb2+ defects in perovskite film by forming PbSO4 in situ, which can cover on the surface and grain boundaries of perovskite to ensure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…1), the binding energy of the Pb 4f 7/2 and Pb 4f 5/2 state of the perovskite lm decreases from 138.71 eV and 143.61 eV to 137.95 eV and 142.8eV after DA 2 SO 4 treatment, which further indicates the interaction between Pb 2+ and SO 4 2− . 31 Fig. 1c shows the cross-sectional scanning electron microscopy (SEM) image of the fabricated p-MPSC, the mp-TiO 2 and mp-ZrO 2 layers are compactly lled with perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…1), the binding energy of the Pb 4f 7/2 and Pb 4f 5/2 state of the perovskite lm decreases from 138.71 eV and 143.61 eV to 137.95 eV and 142.8eV after DA 2 SO 4 treatment, which further indicates the interaction between Pb 2+ and SO 4 2− . 31 Fig. 1c shows the cross-sectional scanning electron microscopy (SEM) image of the fabricated p-MPSC, the mp-TiO 2 and mp-ZrO 2 layers are compactly lled with perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…where ε 0 represents the vacuum dielectric constant, ε is the dielectric constant of the perovskite, V TFL corresponds to the trap-filled limit voltage, e denotes the elementary charge, and L represents the thickness of the perovskite film. 16,17 The defect density in the control perovskite film is 2.58 × 10 15 cm −3 , higher than the 1.65 × 10 15 cm −3 observed in the target perovskite film. T-TRPL and SCLC results collectively indicate that MMTA effectively reduces the defects of the perovskite films and improves the quality of the perovskite film.…”
mentioning
confidence: 76%
“…Furthermore, space charge limited current (SCLC) measurements were conducted to assess the defect densities within the perovskite films quantitatively. The typical current–voltage ( I – V ) curves obtained in the absence of light are presented in Figure c and d. The defect density was quantified using the following equation: n t = 2 ε ε 0 V normalT normalF normalL e L 2 where ε 0 represents the vacuum dielectric constant, ε is the dielectric constant of the perovskite, V TFL corresponds to the trap-filled limit voltage, e denotes the elementary charge, and L represents the thickness of the perovskite film. , The defect density in the control perovskite film is 2.58 × 10 15 cm –3 , higher than the 1.65 × 10 15 cm –3 observed in the target perovskite film. T-TRPL and SCLC results collectively indicate that MMTA effectively reduces the defects of the perovskite films and improves the quality of the perovskite film.…”
mentioning
confidence: 99%
“…It has been previously found that a high-quality perovskite film could significantly increase the lifetime of a PSC. 37,38 The high crystallinity indicates that all chemical elements are arranged in an orderly manner, which is not conducive to defects. According to reports in the literature, the defects are vulnerable to the ambient environment and usually become the sites where the degradation of CsPbBr 3 to PbBr 2 starts.…”
Section: Dalton Transactions Papermentioning
confidence: 99%